1967
DOI: 10.1111/j.1365-2133.1967.tb15825.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Dehydrogenase and Succinic Dehydrogenase in Psoriasis

Abstract: RECENT biochemical and histochemical investigations in })soriasi8 have indicated, directly or indirectly, enhanced respiration and glycolysis (Gans. 1962; Braun-Falco, 1958; Rippa and Vignalli, 1958; Leonhardi, 1961 and Hasimoto e( fl?., 19ti4).Of the quantitative studies, those establishing a rise of the respiratory quotient of the epidermis in the psoriatio lesion as compared with the patients normal skin (Braun-Falco, 1958; Leonhardi, 1961; Blazkova, 1963) are most important. Corres}>ondingly, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1967
1967
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…In contrast, the distribution patterns in fat tissue and the horny layer differ from those of epidermis and dermis; LDHS could not be detected in the horny layer (12). In a Discussion Serum and skin LDH levels have been measured in patients with various skin diseases (2)(3)(4)(5)(6)(7)(8); examples include cutaneous malignant and benign tumors, erythroderma, psoriasis vulgaris and viral infections. The association of high levels of serum LDH and liver metastases in advanced stage patients has been emphasized by several authors (10,11).…”
Section: Changes In Eo Ldh and Ige Levels In The Worsened Group (Tabmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the distribution patterns in fat tissue and the horny layer differ from those of epidermis and dermis; LDHS could not be detected in the horny layer (12). In a Discussion Serum and skin LDH levels have been measured in patients with various skin diseases (2)(3)(4)(5)(6)(7)(8); examples include cutaneous malignant and benign tumors, erythroderma, psoriasis vulgaris and viral infections. The association of high levels of serum LDH and liver metastases in advanced stage patients has been emphasized by several authors (10,11).…”
Section: Changes In Eo Ldh and Ige Levels In The Worsened Group (Tabmentioning
confidence: 99%
“…Isoenzyme analysis of LDH indicates the origin of elevated levels (1). Serum LDH levels have also been reported to be elevated in various skin diseases (2)(3)(4)(5)(6)(7)(8). Recent studies (3,4) suggested that serum LDH5 elevations in eczema-associated erythroderma were correlated with the epidermal cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…Im folgenden ergaben sich sodann aus zahlreichen Einzelbestimmungen von Enzymen (2,15,34,35,79,87,94,113) und Substraten (21,31,60,78,113,119) in psoriatisch veränderter Epidermis bzw. in psoriatischen Schuppen Hinweise auf eine Aktivitätssteigerung des Kohlenhydratstoffwechsels.…”
Section: Veränderungen In Der Psoriatischen Epidermisunclassified
“…The superficial layer of the cutis (papillary layer) ex hibits a marked vasodilatation with an inflammatory infiltrate. Sev eral investigators have dem onstrated that nearly all the enzymes th at are present in the epidermis of psoriasis exhibit an enhanced activity, especially of LDH (Halprin, 1966 andNeumann, 1967).…”
Section: Methodsmentioning
confidence: 99%